BCS superconductivity in the van Hove scenario in s and d waves - Ghosh, Angsula [UNESP] (Sociedade Brasileira de Física, 1999)
The effect of including a van Hove singularity in the density of state of a renormalized BCS equation in s and d waves and its appropriateness in describing some properties of high-Tc cuprates in the weak-coupling region are studied in two space dimensions. The specific heat and knight shift as a function of temperature exhibit scaling below the critical temperature in d wave. We also study the jump in the specific heat at the critical temperature Tc in s and d waves, which can have values significantly higher than the standard BCS values and which increases with Tc, as experimentally observed in many d-wave high-Tc materials. The experimental results on the specific heat and knight shift of the Y-123 system are compared with the theoretical predictions.